2021
DOI: 10.1002/jcp.30615
|View full text |Cite
|
Sign up to set email alerts
|

Amphiregulin in cellular physiology, health, and disease: Potential use as a biomarker and therapeutic target

Abstract: Amphiregulin (AREG), which acts as one of the ligands for epidermal receptor growth factor receptor (EGFR), plays a crucial role in tissue repair, inflammation, and immunity. AREG is synthesized as membrane‐anchored pre‐protein, and is excreted after proteolytic cleavage, and serves as an autocrine or paracrine factor. After engagement with the EGFR, AREG triggers a cascade of signaling events required for many cellular physiological processes including metabolism, cell cycle, and proliferation. Under differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 134 publications
0
17
0
2
Order By: Relevance
“…15a, b ). These findings indicate that our iLD-IL-2 dosing regimen induces a shared Day 55 gene expression signature in different cell types, which featured most prominently the upregulation of Cytokine Inducible SH2 Containing Protein ( CISH ), a gene encoding a well-characterised negative regulator of cytokine signalling, and the downregulation of Amphiregulin ( AREG ), a secreted TNF-inducible protein with pleiotropic roles in inflammation 36 . We also noted an enrichment of genes associated with cytokine signalling, most notably in the tumour necrosis factor (TNF) signalling pathway, which in addition to CISH and AREG , also included TNFSF14 , TNFSF10 , STAT1 , SGK1 , NFKBIZ , NFKBIA , DUSP2 , DUSP4 , DUSP5 , RGS1 and TNFAIP3 (Fig.…”
Section: Resultsmentioning
confidence: 84%
“…15a, b ). These findings indicate that our iLD-IL-2 dosing regimen induces a shared Day 55 gene expression signature in different cell types, which featured most prominently the upregulation of Cytokine Inducible SH2 Containing Protein ( CISH ), a gene encoding a well-characterised negative regulator of cytokine signalling, and the downregulation of Amphiregulin ( AREG ), a secreted TNF-inducible protein with pleiotropic roles in inflammation 36 . We also noted an enrichment of genes associated with cytokine signalling, most notably in the tumour necrosis factor (TNF) signalling pathway, which in addition to CISH and AREG , also included TNFSF14 , TNFSF10 , STAT1 , SGK1 , NFKBIZ , NFKBIA , DUSP2 , DUSP4 , DUSP5 , RGS1 and TNFAIP3 (Fig.…”
Section: Resultsmentioning
confidence: 84%
“…14a,b ). These findings indicate that our iLD-IL-2 dosing regimen induces a shared Day 55 gene expression signature in different cell types, which featured most prominently the upregulation of Cytokine Inducible SH2 Containing Protein ( CISH ), a gene encoding a well-characterised negative regulator of cytokine signalling, and the downregulation of Amphiregulin ( AREG ), a secreted TNF-inducible protein with pleiotropic roles in inflammation 38 . We also noted an enrichment of genes associated with cytokine signalling, most notably in the tumour necrosis factor (TNF) signalling pathway, which in addition to CISH and AREG , also included TNFSF14 , TNFSF10 , STAT1 , SGK1 , NFKBIZ , NFKBIA , DUSP2 , DUSP4 , DUSP5 , RGS1 and TNFAIP3 ( Fig.…”
Section: Resultsmentioning
confidence: 84%
“…A particular type of lymphocyte, the innate lymphoid cells (ILCs), may contribute to host resistance toward SARS-CoV-2 infection and promote restoration of tissue damage by producing amphiregulin, a type-II cytokine. 64 These cells are known in animal models to ensure tissue integrity and regulate the innate and adaptive immune response with the effect of decreasing disease severity. 65 In a recent study, Silverstein et al showed that the number of ILCs in the blood of patients with SARS-CoV-2 infection was inversely correlated with age and was lower in men, reflecting a higher risk associated with male sex and older age.…”
Section: Methodsmentioning
confidence: 99%